Archaeological exploration of fortresses and Cossack settlements of the Lower Don, Turkish Azak of the 17th - 18th centuries: a brief historiographical sketch - Klimova K.I. (Cultural Heritage and Modern Technologies)
This article examines the problems and current state of a new direction for Russia, i.e. the archaeology of Modern times. Monuments of fortification art and weapons are the subject of special archaeological explorations. The research of military engineering art, techniques and traditions of fighting on the southern borders is part of a big important problem of the place and role of the lower reaches of the Don in the process of historical development of Russia. Interest in the study of fortifications, including fragments of Modern times firearms with wick and flint ignition batteries, and other necessary attributes of the daily life of the paramilitary population of the studied region has been increasing over the past thirty years. This interest is accompanied by new findings of flintlocks details and numerous rifle flints in the cultural layers of fortresses and forts of the Lower Don of the 17th – 18th centuries, resulted of archaeological excavations. The authors of the article aim to consider the historiography of the issue, based on the results of archaeological expeditions conducted on the territory of the Lower Don.